Modeling Quality Issues in Curriculum Design - Debnath, Roma Mitra; Shankar, Ravi; Kumar, S. (Lambert Academic Publisher, Saarbrücken, Germany, 2012)
Curriculum is a product - a document, which includes details about goals, objectives, content, teaching techniques, evaluation and assessment of academic resources. Successful curriculum development in a technical institute requires involvement of stakeholders namely students, faculty members, prospective employers and the management or authority of the institute. The interest of different stakeholders varies to a great extent. Although the philosophy and approach towards curriculum development are often the sole responsibility of the educators, to others it is perceived as an instrument to include the interests of the society at large. The main objective of this research is to model the quality issues related to the technical curriculum . This research attempts to consider few methods to model these issues. This would help the curriculum to become more effective by blending concerns of stakeholders like industry, management of the institutes and the internal requirements of students and faculty members of technical institutes.